University e-Extension: A Tool to Spread the Aquaponic Model to Contribute to the Innovation of Organic Food Production, With Low Carbon and Water Footprints - Scaglione, María Cristina (2021)
University e-Extension plays a preponderant role in the diffusion and adoption of new food production technologies. The increasing demands of a growing world population are putting increasing pressure on water resources, land use, and ecosystems globally. To promote comprehensive, highly sustainable, and innovative solutions, we chose aquaponics as a model and for the dissemination of ICTs to teachers, students, and family producers. The intensive use of ICTs made it possible to carry out actions remotely and in real time, monitor specific situations, and produce permanent changes in behaviors and activities. The interaction between people from different social and geographical spaces was achieved, linking their cultural realities, and leaving behind the barriers of time and space. In the framework of this new culture, e-Extension has great opportunities to make the most of instruments that enhance the work of extensionists.